Lake Kumphawapi revisited – The complex climatic and environmental record of a tropical wetland in NE Thailand. (April 2016) - Chawchai, Sakonvan; Yamoah, Kweku Afrifa; Smittenberg, Rienk H; Kurkela, Janita; Väliranta, Minna; Chabangborn, Akkaneewut; Blaauw, Maarten; Fritz, Sherilyn C; Reimer, Paula J; Wohlfarth, Barbara
Kumphawapi, which is Thailand's largest natural freshwater lake, contains a >10, 000-year-long climatic and environmental archive. New data sets (stratigraphy, chronology, hydrogen isotopes, plant macrofossil and charcoal records) for two sedimentary sequences are here combined with earlier multi-proxy studies to provide a comprehensive reconstruction of past climatic and environmental changes for Northeast Thailand. Gradually higher moisture availability due to a strengthening of the summer monsoon led to the formation of a large shallow lake in the Kumphawapi basin between >10, 700 and c. 7000 cal. BP. The marked increase in moisture availability and lower evaporation between c. 7000 and 6400 cal. BP favoured the growth and expansion of vegetation in and around the shallow lake. The increase in biomass led to gradual overgrowing and infilling, to an apparent lake level lowering and to the development of a wetland. Multiple hiatuses are apparent in all investigated sequences between c. 6500 and 1400 cal. BP and are explained by periodic desiccation events of the wetland and erosion due to the subsequent lake level rise. The rise in lake level, which started c. 2000 cal. BP and reached shallower parts c. 1400 cal. BP, is attributed to an increase in effective moisture availability. The timing of hydroclimatic conditions during the past 2000 years cannot be resolved because of chronological limitations.